2017
DOI: 10.1007/s10554-017-1248-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound assessment of the effect of laser energy on the arterial wall during the treatment of femoro-popliteal lesions: a CliRpath excimer laser system to enlarge lumen openings (CELLO) registry study

Abstract: The CliRpath Excimer Laser System to Enlarge Lumen Openings (CELLO) registry included patients treated with modified excimer laser catheters for the endovascular treatment of peripheral artery disease affecting the superficial femoral artery (SFA) and proximal popliteal artery. The aim of this study was to assess, via intravascular ultrasound (IVUS) the dissections in the vessel wall following treatment with the laser catheters. IVUS grayscale images from the CELLO registry were systematically reviewed for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A randomized control trial demonstrated the superiority of ELA with PTA versus PTA alone for treating femoropopliteal ISR in mid-term (6-month freedom from target lesion revascularization; 73.5% versus 51.8%, p < 0.005) [10]. With respect to imaging, intravascular ultrasound assessment indicated that ELA of peripheral artery lesions resulted in significant plaque debulking and increased lumen diameter with negligible degree of adventitial layer injury [11]. Angioscopy assessment also visualized the ELA effect of vaporization of thrombi in femoropopliteal in-stent lesions [12].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized control trial demonstrated the superiority of ELA with PTA versus PTA alone for treating femoropopliteal ISR in mid-term (6-month freedom from target lesion revascularization; 73.5% versus 51.8%, p < 0.005) [10]. With respect to imaging, intravascular ultrasound assessment indicated that ELA of peripheral artery lesions resulted in significant plaque debulking and increased lumen diameter with negligible degree of adventitial layer injury [11]. Angioscopy assessment also visualized the ELA effect of vaporization of thrombi in femoropopliteal in-stent lesions [12].…”
Section: Discussionmentioning
confidence: 99%
“…Use of such imaging can help form the treatment strategy, size the vessel so that the appropriate diameter of balloons or stents being placed is chosen, and guide and direct treatments such as angioplasty and atherectomy to minimize vessel wall injury [6,[27][28][29][30][31]. Intravascular imaging also permits assessment of tissue in the region of the procedure in order to determine whether further treatment is necessary to address regions with incomplete treatment or injury resulting from the treatment [30,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The authors described adventitial layer disruption in < 1% of the 1867 post ablation frames assessed by IVUS, which resulted in a secondary patency of 100% at 6 and 12 months, despite a lower percentage of primary patency. Those are very promising results and results from RCT are welcomed [23].…”
Section: Atherectomy and Other Novel Treatmentsmentioning
confidence: 93%